Fish Autophagy Protein 5 Exerts Negative Regulation on Antiviral Immune Response Against Iridovirus and Nodavirus - Li, Chen; Liu, Jiaxin; Zhang, Xin; Wei, Shina; Huang, Xiaohong; Huang, Youhua; Wei, Jingguang; Qin, Qiwei (Frontiers in Immunology, 2019)
Autophagy is an important biological activity that maintains homeostasis in eukaryotic cells. However, little is known about the functions of fish autophagy-related genes (Atgs). In this study, we cloned and characterized Atg5, a key gene in the autophagy gene superfamily, from orange-spotted grouper (Epinephelus coioides) (EcAtg5). EcAtg5 encoded a 275-amino acid protein that shared 94 and 81% identity to seabass (Lates calcarifer) and humans (Homo sapiens), respectively. The transcription level of EcAtg5 was significantly increased in cells infected with red-spotted grouper nervous necrosis virus (RGNNV). In cells infected with Singapore grouper iridovirus (SGIV), EcAtg5 expression declined during the early stage of infection and increased in the late stage. Fluorescence microscopy revealed that EcAtg5 mainly localized with a dot-like pattern in the cytoplasm of grouper cells. Overexpression of EcAtg5 significantly increased the replication of RGNNV and SGIV at different levels of detection, as indicated by increased severity of the cytopathic effect, transcription levels of viral genes, and levels of viral proteins. Knockdown of EcAtg5 decreased the replication of RGNNV and SGIV. Further studies showed that overexpression EcAtg5 activated autophagy, decreased expression levels of interferon related cytokines or effectors and pro-inflammatory factors, and inhibited the activation of nuclear factor κB, IFN-sensitive response element, and IFNs. In addition, ectopic expression of EcAtg5 affected cell cycle progression by hindering the G1/S transition. Taken together, our results demonstrated that fish Atg5 exerted a crucial role in virus replication by promoting autophagy, down-regulating antiviral IFN responses, and affecting the cell cycle.